2014
DOI: 10.1016/j.ejvs.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Abdominal Aortic Aneurysms

Abstract: Epidemiologic evidence suggests that patients with diabetes may have a lower incidence of abdominal aortic aneurysm (AAA); however, the link between diabetes and AAA development and expansion is unclear. The aim of this review is to analyze updated evidence to better understand the impact of diabetes on prevalence, incidence, clinical outcome, and expansion rate of AAA. A systematic review of literature published in the last 20 years using the PubMed and Cochrane databases was undertaken. Studies reporting app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
136
3
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(153 citation statements)
references
References 78 publications
(58 reference statements)
9
136
3
5
Order By: Relevance
“…Our most recent meta-analysis [6] of 19 studies demonstrated a statistically signifi cant slower growth rate in diabetic patients than in non-diabetic patients (unadjusted standardized MD (SMD), -0.32; 95% CI, -0.40 to -0.24; P < 0.00001; adjusted SMD, -0.29; 95% CI, -0.417 to -0.18; P < 0.00001). Taken together, diabetes is independently and negatively associated with both AAA presence [3,4] and growth [5,6], which suggests that decelerated mechanisms regarding the expansion of an existing AAA may be the same as those regarding the initial formation of an AAA. Further investigations are required to elucidate why BMI is not associated with AAA growth despite its trend toward a positive association with AAA presence.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Our most recent meta-analysis [6] of 19 studies demonstrated a statistically signifi cant slower growth rate in diabetic patients than in non-diabetic patients (unadjusted standardized MD (SMD), -0.32; 95% CI, -0.40 to -0.24; P < 0.00001; adjusted SMD, -0.29; 95% CI, -0.417 to -0.18; P < 0.00001). Taken together, diabetes is independently and negatively associated with both AAA presence [3,4] and growth [5,6], which suggests that decelerated mechanisms regarding the expansion of an existing AAA may be the same as those regarding the initial formation of an AAA. Further investigations are required to elucidate why BMI is not associated with AAA growth despite its trend toward a positive association with AAA presence.…”
Section: Discussionmentioning
confidence: 94%
“…An inverse association was also confi rmed by a pooled analysis of the data from smaller prevalence studies on selected populations (OR, 0.59; 95% CI, 0.35 to 0.99; P = 0.05), while no signifi cant results were provided by case-control studies. A significantly lower pooled incidence of new AAA in diabetics was found in six prospective studies (OR, 0.54; 95% CI, 0.31 to 0.91; P = 0.03) [3]. Our more recent meta-analysis [4] of exclusive adjusted estimates from 13 studies also demonstrated that diabetes was independently and signifi cantly associated with a lower prevalence of AAA (OR, 0.59; 95% CI, 0.52 to 0.67; P < 0.00001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations